Geomorphotectonics of Badush Valley Basin using Geographical Information Systems (GIS) - Hussein, Sundas Juma; Al-Nish, Fawaz Hamid Hamou (Al-Adab Journal, 2022)
Morphotectonics is concerned with the structural interpretation of the shapes of the Earth's surface, where the origin of these features and their relationship to the tectonic process resulting from pressure and tension and the nature of the rock formations of basins are studied. This process is one of the basic processes in the formation of many terrestrial manifestations, as the internal processes greatly affect the generation of extreme pressure and control the nature of rock formations in the basin of the study area, as well as the variation of the processes of rise and fall that were the cause of the formation of different land forms, and contributed to the occurrence of Numerous cracks, breaks and fissures in the rock formations that are affected by geomorphological processes.The area is seismically active, as a group of seismic foci are distributed in the study basin, their depths range between (5.1-20) km, some of which correspond to the sites of developed melt pits and are in the process of growth, and some of them are parallel to the regional fault, as the number of developed melt pits is (16). And in the growth phase (85) concentrated in the upper and middle parts of the basin are unstable, which correspond to the areas of weakness, as these parts are tectonically active and are in constant change.The study relied on analyzing the morphotectonic processes of the secondary basins of the Badoush Valley Basin based on the digital elevation model for the region (DEM) and using the program (Arc GIS V.10.8), by applying five geomorphological indicators of modern tectonic activity and demonstrating the subsurface processes in an applied manner based on accurate measurements of the basins. Determining the occurrence of the basin within the modern tectonic activity in the upper and middle parts, which had an impact on the geomorphology of the basin, while in its lower parts it was low and the occurrence of deformation and anomalies on the paths of the water network.